Engineering Thermostable CYP2D Enzymes for Biocatalysis Using Combinatorial Libraries of Ancestors for Directed Evolution (CLADE). Issue 2 (9th January 2019) - Gumulya, Yosephine; Huang, Weiliang; D'Cunha, Stephlina A.; Richards, Katelyn E.; Thomson, Raine E. S.; Hunter, Dominic J. B.; Baek, Jong‐Min; Harris, Kurt L.; Boden, M.; De Voss, James J.; Hayes, Martin A.; Isin, Emre M.; et al.
Abstract: The structure of metabolites of drug candidates must frequently be characterised during drug discovery and development. However, synthesising metabolites with the correct stereoselective modifications can be challenging for chemically complex parent compounds. Biocatalysis using human drug‐metabolising enzymes, such as cytochrome P450 2D6 (CYP2D6) is an alternative to chemical synthesis. However, most natural enzymes are unstable and have poor efficiency, limiting yields in preparative biotransformations. The aim of this study was to develop a library of robust mutant CYP2D enzymes for biocatalysis. The CLADE (combinatorial libraries of ancestors for directed evolution) approach increased the stability of CYP2D mutants obtained by DNA shuffling using three extant CYP2D forms. The resulting mutants showed divergent profiles of activity towards typical CYP2D substrates and included thermostable forms that may be useful for the further evolution of biocatalysts for specific applications. Abstract : In with the old : Enzymes such as cytochromes P450 can catalyze chemically challenging reactions with high regio‐ and stereo‐selectivity but usually need to be stabilized for industrial use. Recombining extant enzymes with the ancestral form provides a straightforward means to generate libraries of thermostable and catalytically diverse biocatalysts.